Understanding the meaning of the lived experience "maternal role" in women with multiple sclerosis and planning a supportive program: a combined exploratory study protocol - Elaheh Mansouri Ghezelhesari; Mohamad Ali Nahayati; Abbas Heydari; Hosein Ebrahimipour; Talat Khadivzadeh (BMC, 2024)
Abstract Background The maternal role is one of the most challenging yet rewarding roles that women experience in their lives. It begins when a woman becomes pregnant, and as the pregnancy progresses, she prepares to fulfill her role as a mother. A woman's health plays a crucial role in her ability to fulfill the maternal role. Multiple sclerosis (MS), as an autoimmune disease, presents unique challenges in achieving this role. Failing to fulfill the maternal role can have lasting consequences for both the mother and the baby. Given the increasing number of women with MS of reproductive age in Iran and the absence of specific programs for this group during pregnancy and postpartum, researchers have decided to develop a supportive program by exploring the meaning of the maternal role and identifying the needs of these women during this period. Methods/materials This study will be conducted in 3 stages. The first stage involves a qualitative study to explore the meaning of the "maternal role" in women with MS through a descriptive and interpretive phenomenological approach based on Van Manen's method. Data will be collected through semi-structured interviews with pregnant women with MS and mothers with MS who have children under one-year-old, recruited from the Multiple Sclerosis Society of Mashhad, Iran. The second stage will involve designing a support program based on the findings of the phenomenological study, literature review, and exploratory interviews. A logical model will guide the development of the program, and validation will be conducted using the nominal group technique. Discussion This study is the first of its kind in Iran to explore the meaning of the maternal role and develop a support program for women with MS. It is hoped that the results of this study will help address the challenges of motherhood faced by these women.